Leptogenesis in realistic flipped SU(5) - Stephen F. King; George K. Leontaris; Luca Marsili; Ye-Ling Zhou (Journal of High Energy Physics)
Abstract We study thermal leptogenesis in realistic supersymmetric flipped SU(5) × U(1) unification. As up-type quarks and neutrinos are arranged in the same multiplets, they exhibit strong correlations, and it is commonly believed that the masses of right-handed (RH) neutrinos are too hierarchical to fit the low-energy neutrino data. This pattern generally predicts a lightest RH neutrino too light to yield successful leptogenesis, with any lepton-antilepton asymmetry generated from heavier neutrinos being washed out unless special flavour structures are assumed. We propose a different scenario in which the lightest two RH neutrinos N 1 and N 2 have nearby masses of order 109 GeV, with thermal leptogenesis arising non-resonantly from both N 1 and N 2. We show that this pattern is consistent with all data on fermion masses and mixing and predicts the lightest physical left-handed neutrino mass to be smaller than about 10−7 eV. The Dirac phase, which does not take the maximal CP-violating value, plays an important role in leptogenesis.